Budget and development at the beginning of the 21st century. Let us understand the past in order to design the future - MĂNESCU, Rareş (Annals of Spiru Haret University. Economic Series, 2010)
In order to formulate the governmental policies, it is important to understand the experience of the past and not to repeat the same errors. The Government needs to analyze the experience of the past in the budgetary field and design a wise policy in accordance with the acquired relevant experience. Exiting the crisis and re-launching the economic growth have been seen by most specialists as becoming possible first of all by means of budgetary policies. A part of them want to be analyzed the main components of budgetary policy from the perspective of the 19th and 20th century valuable thinking. Expansionist fiscal policy is a policy of reduction of taxes and feeds in order to reanimate the economy. It is particularly recommended for the economic re-launch in the conditions of crises such as the one started in 2008. The too high quotas of the taxes are useless and dangerous. They are useless because being too high they will not help equilibrating the budget, on the contrary.